IL-10 mRNA Engineered MSCs Demonstrate Enhanced Anti-Inflammation in an Acute GvHD Model - Cuiping Zhang; Mina Delawary; Peng Huang; Jennifer A. Korchak; Koji Suda; Abba C. Zubair (Cells, 2021)
Mesenchymal stem cells (MSCs) are used in various studies to induce immunomodulatory effects in clinical conditions associated with immune dysregulation such as graft versus host disease (GvHD). However, most of these clinical trials failed to go beyond early phase 2 studies because of limited efficacy. Various methods have been assessed to increase the potency of MSCs. IL-10 is an anti-inflammatory cytokine that is known to modulate immune responses in GvHD. In this study, we evaluated the feasibility of transfecting IL-10 mRNA to enhance MSC therapeutic potential. IL-10 mRNA engineered MSCs (eMSCs-IL10) maintained high levels of IL-10 expression even after freezing and thawing. IL-10 mRNA transfection did not appear to alter MSC intrinsic characteristics. eMSCs-IL10 significantly suppressed T cell proliferation relative to naïve MSCs in vitro. In a mouse model for GvHD, eMSCs-IL10 induced a decrease in plasma level of potent pro-inflammatory cytokines and inhibited CD4+ and CD8+ T cell proliferation in the spleen. In summary, our studies demonstrate the feasibility of potentiating MSCs to enhance their immunomodulatory effects by IL-10 mRNA transfection. The use of non-viral transfection may generate a safe and potent MSC product for treatment of clinical conditions associated with immune dysregulation such as GvHD.